2011
DOI: 10.1007/s11306-011-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain lipid changes after repetitive transcranial magnetic stimulation: potential links to therapeutic effects?

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is increasingly used in the management of neurologic disorders such as depression and chronic pain, but little is known about how it could affect brain lipids, which play important roles in membrane structure and cellular functions. The present study was carried out to examine the effects of rTMS on brain lipids at the individual molecular species level using the novel technique of lipidomics. Rats were subjected to high frequency (15 Hz) stimulation of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…According to our results, Oliveira [ 29 ] found POL changes in cortex and cerebellum after deep chronic stress, sphingolipid and phospholipid metabolism were deeply affected, showing a decrease in: phosphatidylethanolamine, ether phosphatidylcholine, and an increase in lysophosphatidylethanolamine levels similar to Lee et al [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…According to our results, Oliveira [ 29 ] found POL changes in cortex and cerebellum after deep chronic stress, sphingolipid and phospholipid metabolism were deeply affected, showing a decrease in: phosphatidylethanolamine, ether phosphatidylcholine, and an increase in lysophosphatidylethanolamine levels similar to Lee et al [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…For example, rTMS normalized prefrontal dysfunctions and cognitive-related metabolic profiling in aged mice (Wang H. L. et al, 2016 ). Besides, Lee et al ( 2012 ) found that the effects of rTMS are related to changes in the brain lipids. In human studies, it also has been found that rTMS affects cortical metabolism (Bohning et al, 1999 ; Kimbrell et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since ketamine is an inhibitor of NMDA receptors, this suggests that rTMS-induced antinociception is dependent on NMDA receptors and may involve long-term potentiation (LTP) mechanisms [ 250 ]. Lipidomic analysis of the PFC of rats after rTMS indicate loss of plasmalogen species with long-chain polyunsaturated fatty acids, with an increase in their corresponding lysophospholipids, suggesting endogenous release of long-chain fatty acids such as docosahexaenoic acid (DHA) after rTMS [ 251 ]. DHA may be metabolized to resolvin D1 by 15-lipoxygenase-1 (Alox15), which has been shown to play an important role in LTP [ 252 , 253 ] and antinociception [ 252 , 253 ] .…”
Section: Role Of the Pfc In Management Of Chronic Painmentioning
confidence: 99%